Muamalah Fiqh Analysis In The Rules The Public Accounting Code Of Ethics - Aiza Zulmairoh; Annisa Agustira; Renika Septia Putri; Wulan Anis Mawati (Penerbit Jurnal Indonesia, 2023)
This study aims to contribute to determining decisions in an ethical dilemma of an auditor by the rules of fiqh muamalah. The principles of fiqh discussed in this article are the intention of all the charity requirements of an auditor, the intermediary law is the same as the auditor's objective law, the law of origin is lawful, unless there is a proposition that prohibits it, and the law prioritizes rejecting mafsadat rather than taking benefits. The approach in the formulation of this thought uses a literature study by comparing Islamic figures who apply the muamalah fiqh rules in their daily lives with the case of auditors who have not applied muamalah fiqh rules in their work and focus on primary literature. This study proposes the principles of muamalah fiqh to address the auditor's ethical dilemma. The essence of ethical matters is very important in accounting, especially in the context of developing and enhancing the role of the accounting profession to be able to act professionally.